Motivational strategies to improve speaking skills on students of eighth year of basic education at escuela Luis Augusto Mendoza Moreira, La Libertad, Santa Elena province, 2015-2016. - Del Pezo Orrala, Fernando Ricardo (2016)
This research is aimed to students and teachers, in order to improve the speaking skills in class. Motivational strategies are suggesting an opportunity to improve the speaking skills. These resources will allow bettering the English-speaking environment in class. The exploratory and observation methods allowed establishing a difficulty with the English speaking skills the results offer the implementation of the proposal demonstrated a positive increase in the motivation and the speaking activity on students meeting, the expectations of the researcher and learners. This research concerns on improving speaking skills on students of eighth year of basic education at Escuela Luis Augusto Mendoza Moreira, through motivational strategies that will contribute to increase their performance.